The IMPACT of the COVID-19 Pandemic on Prescription Drug Use in Patients with Psoriasis Vulgaris in Germany - Maria Kahn; Steffeni Papukchieva; Elizabeth Jacyshyn-Owen; Stefan Grimm; Markus Eberl; Sebastian Schneeweiss; Marina Otten; Matthias Augustin; Benjamin Friedrich (Adis, Springer Healthcare, 2023)
Abstract Introduction Real-world evidence (RWE) data is increasingly important to generate rapid insights to effectively manage patient populations. Disruptions like the coronavirus disease 2019 (COVID-19) pandemic may negatively impact the choice of medications used for managing chronic diseases such as psoriasis (PSO). Here, we explored the effect of the COVID-19 pandemic on the sales volumes of treatment guideline-based PSO medication in Germany. Methods Patient-level pharmacy dispensing data from the Permea platform, covering approximately 44% of all community pharmacy dispensing in Germany, were analysed from 2019 through to 2021. Patient demographics and PSO indicated medication sales were assessed specifically before and during the pandemic in Germany. Results We included 6,865,852 sold PSO related drugs from April 2019 to March 2021. Medication sales increased during the pandemic compared with before the pandemic for treatment classes of first-line biological and second-line drugs. The increase was observed across all age groups, but monthly variations could not be detected. Furthermore, we observed increased sales in first-line biological and second-line medications when comparing low to high COVID-19 incidence state. Conclusion Throughout the COVID-19 pandemic the PSO indicated medication sales increased for first-line biological and second-line treatment. This shows that despite the pandemic impact, there continues to be an increase in sales volume for biologics. Only German federal states with intermittently very high COVID-19 incidences show a stagnation in sales volume. The reasons for this need to be investigated in further studies to possibly gain a better understanding of the concerns and uncertainties of patients with PSO.